Fabrication of a Ti-supported NiCo2O4 nanosheet array and its superior catalytic performance in the hydrolysis of ammonia borane for hydrogen generation. Issue 11 (15th January 2016) - Liao, Jinyun; Li, Hao; Zhang, Xibin; Feng, Kejun; Yao, Yanling
Abstract : A Ti-supported NiCo2 O4 nanosheet array exhibited high catalytic performance in the hydrolysis of ammonia borane for hydrogen generation. Abstract : The development of low-cost nanocatalysts with high activity, high stability and good reusability towards the hydrolysis of chemical hydrides for hydrogen generation is of great importance and significance in the field of hydrogen energy. In this work, a Ti-supported NiCo2 O4 thin film nanosheet array (NiCo2 O4 /Ti) is fabricated by a facile method, and its catalytic performance in the hydrolysis of ammonia borane for hydrogen production is investigated. It is found that the turnover frequency (TOF) of NiCo2 O4 /Ti can reach 50.1 mol H2 min −1 (mol catalyst) −1, which is the highest TOF value reported for noble-metal-free catalysts towards the hydrolysis of ammonia borane. The apparent activation energy of ammonia borane hydrolysis in the presence of the NiCo2 O4 /Ti catalyst is as low as ca. 17.5 kJ mol −1 . More importantly, the NiCo2 O4 /Ti catalyst can retain ca. 90% of its original catalytic activity after 10 cycles, exhibiting much improved durability and reusability in contrast to many nanocatalysts recently reported in the literature. Its high catalytic activity and low-cost, together with its good durability and reusability, enable NiCo2 O4 /Ti to be a strong catalyst candidate for the hydrolysis of ammonia borane for hydrogen production in the practical applications.